Oral fecal transplantation enriches Lachnospiraceae and butyrate to mitigate acute liver injury - Yang, Chun-Ju; Chang, Hao-Chun; Sung, Pin-Cheng; Ge, Mao-Cheng; Tang, Hsiang-Yu; Cheng, Mei-Ling; Cheng, Hao-Tsai; Chou, Hong-Hsue; Lin, Cheng-Yu; Lin, Wey-Ran; Lee, Yun-Shien; Hsieh, Sen-Yung (Cell reports (Cambridge), 2024)
While fecal microbiota transplantation (FMT) shows promise in treating human diseases, oral capsule FMT is more accepted and accessible to patients. However, microbe selection in the upper gastrointestinal tract (UGIT) through oral administration remains unclear. Here, we demonstrate that short-term oral fecal gavage (OFG) alleviates acetaminophen-induced acute liver injury (AILI) in mice, regardless of the divergent effects of commensal gut microbes. Pasteurized fecal gavage yields similar therapeutic effects. OFG enriches gut Lachnospiraceae and butyrate compared to donor feces. Butyrate mitigates AILI-induced ferroptosis via AMPK-ULK1-p62 signaling to simultaneously induce mitophagy and Nrf2 antioxidant responses. Combined N-acetylcysteine and butyrate administration significantly improves AILI mouse survival rates. These observations indicate the significance of the UGIT in modulating the implanted fecal microbes through oral administration and its potential biological and clinical impacts. Our findings also highlight a possible strategy for applying microbial metabolites to treat acute liver injury. [Display omitted] •Oral fecal gavage (OFG) or pasteurized fecal gavage (OPG) mitigates AILI in mice•OFG and OPG enrich gut Lachnospiraceae and butyrate by UGI tract•Butyrate suppresses ferroptosis via activating AMPK-P62-Nrf2 signaling and mitophagy•Combined N-acetylcysteine and butyrate therapy significantly reduces AILI mortality Yang et al. show that oral fecal gavage (OFG) reshapes gut microbiota, protecting mice from acetaminophen-induced liver injury (AILI). OFG enriches gut Lachnospiraceae and butyrate. Butyrate counteracts AILI-related ferroptosis through Nrf2 antioxidant signaling and mitophagy, highlighting upper gastrointestinal tract microbial selection and potential for microbial metabolites in AILI treatment.